2012
DOI: 10.1001/archophthalmol.2012.371
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary Choroidal Thickness in Healthy Controls and Patients With Focal, Diffuse, and Sclerotic Glaucomatous Optic Disc Damage

Abstract: The peripapillary choroid of patients with glaucoma who have sclerotic optic disc damage was approximately 25% to 30% thinner compared with that in patients with focal and diffuse optic disc damage and with that in healthy controls. The role of the choroid in the pathophysiology of sclerotic glaucomatous optic disc damage needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
77
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 27 publications
16
77
0
3
Order By: Relevance
“…16,17 Studies have noted that choroidal circulation was abnormally reduced (i.e., deficient peripapillary choroidal filling on fluorescein angiography) 18e21 and that choroidal thickness was decreased in glaucomatous eyes. 22,23 Choroidal thinning might be due to the loss of the innermost choroidal vasculature, and it might be related to juxtapapillary choroidal insufficiency, resulting in glaucomatous retinal ganglion cell damage. 24,25 Sullivan-Mee et al 8 recently showed that juxtapapillary choroidal volume was decreased in POAG eyes with b-zone PPA and suggested that b-zone PPA might be a biomarker for juxtapapillary choroidal atrophy and associated vascular compromise in glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Studies have noted that choroidal circulation was abnormally reduced (i.e., deficient peripapillary choroidal filling on fluorescein angiography) 18e21 and that choroidal thickness was decreased in glaucomatous eyes. 22,23 Choroidal thinning might be due to the loss of the innermost choroidal vasculature, and it might be related to juxtapapillary choroidal insufficiency, resulting in glaucomatous retinal ganglion cell damage. 24,25 Sullivan-Mee et al 8 recently showed that juxtapapillary choroidal volume was decreased in POAG eyes with b-zone PPA and suggested that b-zone PPA might be a biomarker for juxtapapillary choroidal atrophy and associated vascular compromise in glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…The choroid exhibited a similar pattern in controls and patients with POAG; it was GON [7,8] , results of the involvement of the peripapillary choroid and GON are mixed. Some authors reported a reduction in the mean or regional peripapillary choroidal thickness (PPCT) in primary open-angle glaucoma (POAG), especially in association with sclerotic optic disk damage [9] and normal tension glaucoma [10,11] . Others found no differences among glaucoma, healthy, and glaucoma-suspect eyes with regard to peripapillary choroidal structures [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…Bisher gibt es einige Publikationen, die eine Assoziation von pAD und Glaukom mittels SD-OCT analysierten, allerdings mit widersprüchlichen Resultaten [12,13,15,[18][19][20]. In der vorgestellten Pilotstudie wurde die pAD in unterschiedlichen Abständen zur Papille bei kaukasischen POWG-Probanden mit Augengesunden verglichen.…”
Section: Hintergrundunclassified
“…In den genannten Publikationen wurden die Glaukomprobanden anhand der Papillenexkavation und des perimetrischen Befunds eingeteilt. Eine gänzlich andere Einteilung anhand des fundusskopischen Befundes nahmen Roberts et al vor [20]. In deren Studie waren Probanden mit Offenwinkelglaukom, Pseudoexfoliations-und Pigmentdispersionsglaukom eingeschlossen und wurden nach lokal begrenzter, diffuser und sklerotischer Optikusatrophie eingeteilt.…”
Section: Diskussionunclassified
See 1 more Smart Citation